Affective map of Rocas neighborhood – Natal, Brazil - de Lima Pereira, Arthur Leonardo (2024)
This work, conducted at the Núcleo de Antropologia Visual (NAVIS/UFRN), aims to carry out an anthropological research to create an Affective Map of the Rocas neighborhood, located in the East Zone of Natal, in the state of Rio Grande do Norte, Brazil. The affective map, guided by emotions, seeks to open spaces for counter-hegemonic narratives. The choice of the Rocas neighborhood follows previous research by NAVIS, which investigates tensions in the historic neighborhoods of Natal. For this work, we will use methods such as image capture, walks, assemblages, and (re)assemblages of maps. Thus, we position ourselves from knowledge that questions Eurocentric rationality, proposing confrontations to this unique, modern, capitalist, and Western episteme. The project seeks to diversify the ways of sharing results and contribute to a broader understanding of urban and visual experiences.